2022
DOI: 10.1111/gcb.16281
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem health, ecosystem services, and the well‐being of humans and the rest of nature

Abstract: An ecosystem is healthy if it is active, maintains its organization and autonomy over time, and is resilient to stress. Healthy ecosystems provide human well‐being via ecosystem services, which are produced in interaction with human, social, and built capital. These services are affected by different ecosystem stewardship schemes. Therefore, society should be aiming for ecosystem health stewardship at all levels to maintain and improve ecosystem services. We review the relationship between ecosystem health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(11 citation statements)
references
References 93 publications
0
10
0
1
Order By: Relevance
“…Thus, the VORS (vigor‐organization‐resilience‐ecosystem service) framework further refines regional ecosystem health measurement. However, Hernández‐Blanco et al (2022) pointed out that healthy ecosystems are linked to human social and economic development through the provision of ecosystem services, and the relationship between the two is complex. In view of the above controversies, this paper adopted a traditional VOR method to assess ecosystem health status.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the VORS (vigor‐organization‐resilience‐ecosystem service) framework further refines regional ecosystem health measurement. However, Hernández‐Blanco et al (2022) pointed out that healthy ecosystems are linked to human social and economic development through the provision of ecosystem services, and the relationship between the two is complex. In view of the above controversies, this paper adopted a traditional VOR method to assess ecosystem health status.…”
Section: Discussionmentioning
confidence: 99%
“…In the prevailing discourse of One Health, the intrinsic value of nature is debated, but to satisfy the current, evidence-based policy processes, the value of nature is translated into ecosystem-services (to humans) which are then given an economic value (Costanza et al, 1997 ). However, building on a logic that healthy ecosystems provide human well-being via ecosystem services, a review of the Ecosystem Services Valuation Database found that approximately 58% of the records data on ecosystem health were lacking (Hernández-Blanco et al, 2022 ). Independently, the re-emergence of ecological perspectives in human and animal health originating from environmental psychology, human geography, and other disciplines, provides abundant evidence supporting the health benefits from nature rather than risks (Locke et al, 2021 ; Nishi & Hashimoto, 2022 ), and fuel the need to reconsider our relationship to nature (Zu Ermgassen et al, 2022 ).…”
Section: Recent One Health Developmentsmentioning
confidence: 99%
“…Ecosystem degradation can decrease the availability of ecosystem services, making it a crucial indicator of ecosystem health [44]. In 2021, the Department of Natural Resources of Hubei Province released the 'Hubei Provincial Ecological Restoration Plan (2021-2035),' which outlines the most urgent ecological issues and challenges faced by the Hubei Province.…”
Section: Research Frameworkmentioning
confidence: 99%